Antiosteoporosis and bone protective effect of dieckol against glucocorticoid-induced osteoporosis in rats - Wang, Hao; Yang, Leigang; Chao, Junwei (Frontiers in Endocrinology, 2022)
Background Glucocorticoids (GCs) induce osteoporosis, which results in fractures in the bond, causing significant morbidity. In the conducted study, we examined the antiosteoporosis effect of dieckol against GC-induced osteoporosis in rats. Methods Sprague–Dawley (SD) rats were used for the current study and dexamethasone (2.5 mg/kg) induced osteoporosis in the rats that received the dieckol (test) and alendronate (standard) for 20 weeks. Bone turnover parameters, microCT, antioxidant, inflammatory cytokines, nutrient, and hormones parameters. Results Dieckol noticeably suppressed the body weight and boosted the uterine and vagina weight. Dieckol considerably altered the level of trabecular number (Tb. N), the bone volume to total volume (BV/TV), trabecular separation (Tb.Sp), bone surface to bone volume (BS/BV), and t​r​a​b​e​c​u​l​a​r thickness (Tb.Th). Dieckol noticeably (P < 0.001) elevated the level of osteocalcin (OC) and alleviated the level of bone Gla protein (BGP), acid phosphatase (ACP), alkaline phosphatase (ALP), and β-CTx. Dieckol markedly boosted the level of malondialdehyde (MDA) and suppressed the level of glutathione (GSH), catalase (CAT), and superoxide dismutase (SOD) along with the suppression of inflammatory cytokines like TNF-α, IL-1β, and IL-6. Dieckol remarkably increased the level of calcium, potassium, magnesium, and 25 (OH) vitamin D. Dieckol substantially (P < 0.001) boosted the level of estradiol and alleviated the level of parathyroid hormone and tartrate-resistant acid phosphatase (TRAP). Dieckol also suppressed the level of receptor activator of nuclear factor κB ligand (RANKL) and boosted the level of osteoprotegerin (OPG). Conclusion Taken together, our data suggest that dieckol demonstrated the anti-osteoporosis effect against GC-induced osteoporosis in rats.